A Racial Injustice In Nic Stone’s Dear Martin - Ananda, Kresna Dwi; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This thesis is entitled A Racial of Injustice in Nic Stone’s Dear Martin. The study analyzes how racial injustice is depicted through the narrative structure of the novel. The study aims to describe the narrative structure of racial injustice, identify forms of systemic racism, and analyze their impact on the main character, Justyce McAllister. The data are taken from the novel as the primary source. The study employs a qualitative research method with a narrative analysis approach. Because the issue relates to structural social problems, the researcher applies Tzvetan Todorov’s narrative theory and Joe Feagin’s systemic racism theory. The results show that the narrative follows five stages: equilibrium, disruption, recognition, an attempt to repair, and a new equilibrium. The study also reveals three forms of systemic racism: structural, institutional, and cultural. These forms of racism are embedded in education, law enforcement, the media, and social perceptions. Justyce experiences emotional trauma, an identity crisis, and social alienation due to racism. Despite facing discrimination, Justyce rebuilds his identity and resilience by reflecting on his experiences through letters to Dr. Martin Luther King Jr. In the end, the novel portrays how racism affects every aspect of life and identity and demonstrates how narrative can be used to critique and challenge social injustice.